2022
DOI: 10.1186/s40468-022-00188-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and language improvement: the effect of peer assessment (PA) on reading comprehension, reading motivation, and vocabulary learning among EFL learners

Abstract: Assessment is an inseparable part of teaching and learning, and it helps teachers and students to modify their teaching and learning processes. One type of assessment is peer assessment (PA), and its effects were examined on developing Iranian EFL learners’ reading comprehension (RC), reading motivation (RM) and vocabulary learning (VL) in this research. To achieve this goal, 60 Iranian EFL students at the intermediate level and with the age range of 18 to 26 years were selected based on a convenience sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…It takes time and effort to encourage learners' reading habits. Learners must be motivated to develop positive reading habits by according them with access to a diverse range of books (Ali et al, 2021;Awah, 2021;Barber & Klauda, 2020;Brå ten et al, 2022;Gunobgunob-Mirasol, 2019;Jodeck-Osses et al, 2021;Kazemi et al, 2020;Locher & Pfost, 2020;Meniado, 2021;Neisi et al, 2019;Nevo et al, 2020;Ritonga et al, 2022;Sun, 2023;Torppa et al, 2020;Xia et al, 2019;Xin & Yunus, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It takes time and effort to encourage learners' reading habits. Learners must be motivated to develop positive reading habits by according them with access to a diverse range of books (Ali et al, 2021;Awah, 2021;Barber & Klauda, 2020;Brå ten et al, 2022;Gunobgunob-Mirasol, 2019;Jodeck-Osses et al, 2021;Kazemi et al, 2020;Locher & Pfost, 2020;Meniado, 2021;Neisi et al, 2019;Nevo et al, 2020;Ritonga et al, 2022;Sun, 2023;Torppa et al, 2020;Xia et al, 2019;Xin & Yunus, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Ritonga et al (2022) looked at how peer evaluation affected the growth of Iranian EFL learners' , reading motivation (RM), vocabulary learning (VL), and reading comprehension (RC). To accomplish this, 60 Iranian EFL learners were chosen and separated into two groups: the CG and EG.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Anent this, Ritonga [7] stressed that giving support and feedback helped the students to improve their language learning. Likewise, ONeil [8] found that students receiving feedback mechanism responded more positively and more satisfied with the advice they received.…”
Section: Level Of Language Learning Self-efficacymentioning
confidence: 99%